Предмет: Математика,
автор: koncevicm3
Решите уравнение -x(2x-1)-(x-3)(3+x)+ 3x во второй степени = 10
Ответы
Автор ответа:
0
-x(2x-1)-(x-3)(3+x)+ 3x^2 = 10
-2х^2+х-(3х+х^2-9-3х)+3х^2=10
-2х^2+х-3х-х^2+9+3х+3х^2=10
Приводим подобные слагаемые :
Х+9=10
Х=10-9
Х=1
Ответ: 1
-2х^2+х-(3х+х^2-9-3х)+3х^2=10
-2х^2+х-3х-х^2+9+3х+3х^2=10
Приводим подобные слагаемые :
Х+9=10
Х=10-9
Х=1
Ответ: 1
Похожие вопросы
Предмет: Физика,
автор: Gfej5338hgf
Предмет: Геометрия,
автор: denus36015
Предмет: Химия,
автор: q1wq11w
Предмет: Алгебра,
автор: БПАН116rus
Предмет: Литература,
автор: ВведитеСвойЕМайл